ASSOCIATIONS BETWEEN PERCEIVED SOCIAL SUPPORT FROM TEAMMATES AND ATHLETE'S BURNOUT IN FUTSAL PLAYERS - Luthfi Ahmad Nurhaqqi, - (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2023)
Researchers have found that the maladaptive experience of exercise called burnout is a determining factor in athletes' athletic development and performance. To reduce or mitigate the burnout phenomenon, research examines the relationship between social support provided by teammates and athlete burnout in futsal players. This research is expected to find aspects of social support that have the greatest role in preventing athletes' burnout experiences. This type of research is descriptive correlation. The sample used was 20 UKM Futsal UPI athletes who had participated in national competitions. Social support was measured using the Social Provisons Scale and adapted to refer specifically to teammates as a source of support and athlete burnout was measured using the Athlete Burnout Questionnaire. Based on the research results, it found that social support and burnout had a correlation coefficient of -0.490 with a Sig value. of 0.028. This means that there is a negative correlation between social support and burnout in futsal athletes. And based on the regression test carried out, the attachment aspect of social support is the most dominant aspect in preventing burnout in futsal athletes.